Identity, instability, and investors: An empirical investigation of the home bias - Thilo R. Huning; Fabian Wahl (Humboldt University Berlin, 2022)
In this paper, we present novel data from the German-speaking area on 13,422 venture capital investments between 1999 and 2019, and document a novel and yet unexplained contributor to investors' home bias. We propose a new measure of regional identity based on a recent vehicle license plate liberalization in Germany, and leverage on a unique dataset of historical borders to show how regional identity is formed. We use an instrumental strategy to establish a causal link between historical political instability, regional identity, and the home bias. Our results indicate that a common regional identity is highly relevant for investment decisions.
urn:nbn:de:kobv:11-110-18452/26058-9
Keywords: G11; G24; G41; N20; Z19; 330; home bias; venture capital; start-ups; investor behavior; common regional identity; historical political instability